Ewing`s Sarcoma - Agnieszka Budny (Journal of Education, Health and Sport, 2017)
Ewing's sarcoma is a small round-cell tumor typically arising in the bones, rarely in soft tissues, of children and adolescents. Clinical presentation is usually dominated by local bone pain and a mass. Magnetic resonance best defines the extent of the lesion. Patients diagnosed with Ewing's sarcoma within  last years show a improving  survival rate . Rehabilitation seems to be a crucial part of multimodal therapy.